1980
DOI: 10.1051/jphyslet:019800041021049900
|View full text |Cite
|
Sign up to set email alerts
|

E.P.R. investigations of commensurate-incommensurate structural phase transitions through « forbidden hyperfine lines ». Application to Rb2ZnCl4 : Mn2+

Abstract: 2014 L'examen détaillé de la structure hyperfine d'une transition électronique-1 2 ~ 1 2, pour une sonde paramagnétique avec S ~ 3/2, semble bien adapté à l'étude des phases incommensurables. On illustre la méthode dans le cas de Rb2ZnCl4 : Mn2+. Abstract. 2014 A detailed investigation of the hyperfine structure of the-1/2 ~ 1/2 electronic transition, for a paramagnetic probe with S ~ 3/2, seems to be well adapted to the study of incommensurate phases. We exemplify the method in the case of Rb2ZnCl4 : Mn2+.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

1981
1981
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 7 publications
2
14
0
Order By: Relevance
“…The g-factor, g, and the hyperfine constant, A, are nearly isotropic [27] with values g = 2.004 and A = 9.0 mT [28], while the fine structure tensor D is very sensitive to the local environment of the Mn 2+ ion. The superposition model by Newman et al [29][30][31][32][33][34][35] expresses D in terms of additive uniaxial crystal field contributions from the nearest neighbor ions,…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The g-factor, g, and the hyperfine constant, A, are nearly isotropic [27] with values g = 2.004 and A = 9.0 mT [28], while the fine structure tensor D is very sensitive to the local environment of the Mn 2+ ion. The superposition model by Newman et al [29][30][31][32][33][34][35] expresses D in terms of additive uniaxial crystal field contributions from the nearest neighbor ions,…”
Section: Experimental Methodsmentioning
confidence: 99%
“…As line position data have shown, for orientation Bā = 7 • both linear and quadratic terms in (1) and so in (4,5) have to be accounted. The local line width involves secular and non-secular contributions which originate from linear and quadratic terms in (1) and measure the fluctuations spectrum at zero frequency and EPR frequency correspondingly [14].…”
Section: Epr Line Width Broadening Near T Imentioning
confidence: 99%
“…Spectral contour have been simulated by integrating of 2π 0 L[ B−B r (ϕ 0 ) δB(ϕ 0 ) ]dϕ 0 , where position of individual lorenzian B r (ϕ 0 ) is determined from static part of expansion (1) and local line width δB(ϕ 0 ) depends on phase in accordance with (4,5).…”
Section: Epr Line Width Broadening Near T Imentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations of the orientational diagrams of the ESR fine structure have shown that Mn 2+ centers, substituting Zn 2+ ions, are localized in chloride tetrahedra. Detection of the forbidden hyperfine doublets (∆m J = ± 1) on passing through paraelectric-incommensurate phase transition unequivocally indicates that Mn 2+ is an appropriate paramagnetic probe and it is very sensitive to (ZnCl 4 ) group rotations associated with incommensurate structural modulation [4].…”
Section: Introductionmentioning
confidence: 99%